2019
DOI: 10.1039/c9tx00089e
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic study of vitamin B6 on hyperglycaemia induced protein carbonylation, DNA damage and ROS production in alloxan induced diabetic rats

Abstract: Study of nutraceutical and food supplements especially vitamins against diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Muellenbach and coworker [113] demonstrated that the combined treatment of PM and alpha lipoic acid (a powerful antioxidant molecule) resulted in a substantial reduction of the oxidative stress biomarkers in obese Zucker rats. More recently Abdullah and coworkers [114] demonstrated that PM supplementation in alloxan-induced diabetic rats caused a significant decrease in both oxidative stress parameters and ROS production, and consequently reduced DNA damage.…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
“…Muellenbach and coworker [113] demonstrated that the combined treatment of PM and alpha lipoic acid (a powerful antioxidant molecule) resulted in a substantial reduction of the oxidative stress biomarkers in obese Zucker rats. More recently Abdullah and coworkers [114] demonstrated that PM supplementation in alloxan-induced diabetic rats caused a significant decrease in both oxidative stress parameters and ROS production, and consequently reduced DNA damage.…”
Section: Vitamin B6 and Diabetes Complicationsmentioning
confidence: 99%
“…Endogenous AGEs abundancy can be influenced by the diet, in particular, the amount of reducing sugars in the diet [ 14 , 15 ]. Diet rich in antioxidants leads to decreased AGEs formation both in vitro and in vivo, implicating redox regulation and blood glucose as potential modulatory factors [ 16 , 17 ]. Quercetin (QUE), a plant flavonoid, has antioxidant properties and leads to the inhibition of AGEs formation [ 17 ], and has shown a beneficial effect in diabetes, neurodegenerative diseases and addiction [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence associates vitamin B6 with diabetes, indicating that its deficiency can induce insulin resistance, while its supplementation can restore normal blood glucose levels (Abdullah et al, 2019; Fields et al, 2021; Kim et al, 2018). However, underlying mechanisms are still unknown.…”
Section: Resultsmentioning
confidence: 99%